2003
DOI: 10.1037/0882-7974.18.2.181
|View full text |Cite
|
Sign up to set email alerts
|

The costs of doing two things at once for young and older adults: Talking while walking, finger tapping, and ignoring speech of noise.

Abstract: Young and older adults provided language samples in response to questions while walking, finger tapping, and ignoring speech or noise. The language samples were scored on 3 dimensions: fluency, complexity, and content. The hypothesis that working memory limitations affect speech production by older adults was tested by comparing baseline samples with those produced while the participants were performing the concurrent tasks. There were baseline differences: Older adults' speech was less fluent and less complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
153
3
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 69 publications
12
153
3
4
Order By: Relevance
“…Recent work by Kemper et al [29] underscores the issue of task priority: in this study, young and older adults spoke on topics of general knowledge while walking at a comfortable pace, finger tapping, or ignoring extraneous noise. Speech samples were analyzed in terms of grammatical complexity, sentence length, and content.…”
Section: Experimental Evidencementioning
confidence: 86%
See 1 more Smart Citation
“…Recent work by Kemper et al [29] underscores the issue of task priority: in this study, young and older adults spoke on topics of general knowledge while walking at a comfortable pace, finger tapping, or ignoring extraneous noise. Speech samples were analyzed in terms of grammatical complexity, sentence length, and content.…”
Section: Experimental Evidencementioning
confidence: 86%
“…In contrast to earlier studies, this literature has also examined more complex cognitive tasks such as walking while talking [29] or walking while memorizing words using mental imagery [31,38].…”
Section: Experimental Evidencementioning
confidence: 99%
“…For both of these participant groups, Pohl et al (2011) found no significant difference in the conversational speech rate between the walking and not walking conditions. In contrast, Kemper, Herman, and Lian (2003) investigated conversational speech rate in healthy older adults and found a significant reduction in conversation speech rate while performing concurrent finger tapping or walking tasks.…”
Section: Conversational Speech Ratementioning
confidence: 98%
“…Both the Ho et al (2002) and Kemper et al (2003) studies used concurrent manual tasks. On the other hand, the Pohl et al (2011) study used a concurrent walking task and they elicited conversational speech using a methodology that was very similar to that of the present study.…”
Section: Conversational Speech Ratementioning
confidence: 99%
“…The rate of the sequential tapping was self-paced, and the subjects were instructed to stop after touching each finger once. The finger tapping part of this paradigm was designed to control for the auditory prompt used in VG and to distract the subjects from performing verb generation, as this type of activity is relatively incompatible with continued engagement in verbal processing; finger tapping is known to decrease the ability to generate fluent speech in adults [39,40]. Monitoring finger tapping via closed-circuit TV also provided a gross assessment of task performance by the subjects.…”
Section: Verb Generation Task (Vg)-mentioning
confidence: 99%